(untitled) (Revista Brasileira Multidisciplinar, 2024)
Compared to traditional dressings, bacterial cellulose (BC) membranes have interesting characteristics in the treatment of skin lesions, such as: immediate pain relief, maintenance of local humidity, action as a protective physical barrier, and adsorption of exudates during the inflammatory phase; however, they do not have intrinsic antibacterial properties. As far as drug release systems are concerned, BC presents a model of rapid release of the active ingredient ("burst release") which has negative effects and can be pharmacologically dangerous. The aim of this work is to obtain composites based on BC and Laponite clay organofunctionalized with amino groups in order to develop a new material that can serve as a precursor to multifunctional dressings with antibacterial action and a controlled drug release system. Infrared vibrational spectroscopy showed bands referring to the -NH2 and Si-O groups of the silane and clay structure, respectively, thus indicating the presence of these components in the sample. In addition, the modification of cellulose led to structural changes in the crystalline regions of BC. The presence of surface granules on the fibers, a reduction in thermal stability and a change in water vapor permeation were observed, compared to pristine BC, indicating success in modifying the polymer.